Exploring the acceptance of mozzarella cheese in school lunches among school-aged children: a pilot study - Lin, Xiaofang; Zhang, Qin; Wu, Qiong; Huo, Wenxuan; Zhang, Xiaoying; Geng, Shanshan; Lv, Yizhou; Li, Yuanyuan; Wang, Yilun; Dong, Linjing; Leng, Xue; Lin, Zhenghao; et al. (Frontiers in Nutrition, 2025)
IntroductionDairy products are an important source of high-quality protein, calcium, vitamin A, and other nutrients, and they are a crucial part of a balanced diet for children. However, the daily intake of dairy products among school-age children in China is significantly inadequate. Considering school lunches as a vital pathway for children to obtain nutrients, this study aims to develop school lunch dishes incorporating mozzarella cheese and to assess the acceptance of these dishes among school-age children.MethodsThis study was carried out in a primary school which has a self-run canteen in Nanjing. We innovatively integrated cheese with traditional Chinese food, and conducted a 3-month pilot study to develop dishes that meet the nutritional needs and sensory experience of students. 121 students with an average age of 9.8 years were invited to assess each dishes’ appearance, aroma, taste and overall liking, by using a 5-point Likert Scale. Focus group discussions were conducted after the project to further discover students’ attitude toward cheese dishes and canteen cooks’ experience in improving cheese dishes.ResultsDuring the program, 16 cheese dishes were made, including 3 steamed dishes, 2 ready-to-eat foods (only heating required), and 11 stir-fried dishes. The overall liking’ results showed that ready-to-eat foods were the most popular among students, and steamed dishes ranked higher than stir-fried dishes (P < 0.001). Among the stir-fried dishes, students’ liking scores differed for cheese dishes made from different raw materials, pure meat food was more popular than vegetable food (P = 0.003), meat and vegetable food (P = 0.012). Additionally, focus group discussions found that students gave more positive ratings to and ready-to-eat foods and steamed dishes.ConclusionCheese can be well combined with traditional Chinese ingredients and be accepted, especially steamed or combined with meat. Introducing cheese in school lunches not only helps cultivate a habit of consuming cheese among children and adolescents from a young age, but also aids in closing the gap between their dairy consumption and dietary guidelines.